PERAN COALITION FOR ORGAN-FAILURE SOLUTIONS (COFS) DALAM PENANGGULANGAN ORGAN TRAFFICKING DI INDIA - Rahayu, Vina; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study analyzes the role of Coalition for Organ-Failure Solutions (COFS) inovercoming organ trafficking in India. COFS has an important role for fight againstorgan trafficking in India. Organ trafficking become a transnational crime that is athreat to crimes against humanity. COFS is a non-profit international health and humanrights organization with a mission to end organ trafficking and accountable channelsbased on social justice and equity. India was one organ trafficking hotspots in theworld.This research used qualitative method which is done explained the cased basedon existing facts. The techniques used to collects data to study the case to libraryresearch in the form journals, books, official document, reports and website. Thetheoretical framework applied in this research are pluralism perspective, level ofanalysis group behaviour and theories used in this study based on the role ofinternational organization theory by Clive Archer.This research resulted the role to overcome organ trafficking in India. COFSimplement some major programs, there are some programs conducted by COFS. Theseprograms are outreach programs, creating public awareness and conducting researchon victims. This programs has big impact to victims of organ trafficking in India.Through the programs, COFS can reduce organ trafficking in India.Keyword: Role, COFS, Organ Trafficking, India